Factors associated with gestational diabetes mellitus in pregnant women treated at aMaternal Perinatal Institute - Torres Tello, Paula Rosa (2026)
Introduction. Gestational diabetes mellitus (GDM) increases the risk of maternal and perinatal complications.Objective. To identify factors associated with GDM in pregnant women treated at the Instituto Nacional MaternoPerinatal. Methods. An unmatched case–control study (1:1) was conducted in 126 pregnant women with singletonpregnancies, aged 15 years or older. Data was obtained from medical records, and participants were selected usingconsecutive non-probabilistic sampling. Maternal factors and obstetric history were evaluated. Bivariate analysis andbinary logistic regression were applied to estimate crude (cOR) and adjusted odds ratios (aOR). Results. In themultivariate analysis, family history of diabetes (aOR: 11.03; 95% CI: 2.75–44.32) and pregestational obesity (aOR:3.03; 95% CI: 1.20–7.66) were the only factors associated with GDM. Conclusion. Family history of diabetes andpregestational obesity were the main factors associated with GDM; therefore, their early identification could strengthenscreening and preventive interventions during prenatal care.